A prospective study on the quantification of anti-HBs antibody titers of vaccinated health care workers in a tertiary care teaching hospital by using automated enzyme linked fluorescent assay - Indernath, Sunil; K., Sudha; N., Shanmugavadivoo; B., Usha; S., Vinod Babu (International Journal Of Community Medicine And Public Health, 2022)
Background: Hepatitis B virus (HBV) infection poses a major health problem among health care workers (HCWs). Globally, 350 million peoples have infected, and it was estimated by WHO. CDC has recommended HBV vaccination for all health care workers. The objective was to determine the anti-HBs antibodies titres among health care workers using automated enzyme linked fluorescent assay (ELFA). Methods: This prospective study was conducted in department of microbiology, tertiary care hospital. The test samples have been collected from health care workers who have completed the course of vaccination. VIDAS anti-HBs total II (AHBS) assay was initiated according to the manufacturer’s instructions. Results: Out of 100 subjects, 62% showed positive for anti-HBs antibodies and the remaining 38% showed negative. Positivity of anti-HBs antibody titers ranges from 27 mIU/ml to 500 mIU/ml. Conclusions: In the present study, 100 subjects have been selected based on the HBV vaccination with completion of three doses of vaccination. Presence of anti-HBs antibodies titers against the vaccination is fully immunized. The study was determined the vaccinated status of anti-HBs antibodies against the infection among clinicians, nurses and CRRIs and it has to be revealed at regular intervals of every 6 to 8 months.